Price limit bands, risk-return trade-offand asymmetric volatility: Evidence fromTunisian Stock Exchange sectors - Mnari, Othman; Faouel, Bassma (Economics and Business Review, 2024)
This paper explores the impact of imposing various price limit bands on risk-return trade-off and asymmetric volatility on the Tunisian Stock Exchange (TSE). The study applies the EGARCH-M approach during the period spanning from 2 January 2019 to 31 January 2024, covering the periods before, during, and after the COVID-19 era. During the COVID-19 period, the TSE reduced the per-session price limit to protect investors from severe price fluctuations. Despite this protective measure, the results show that higher volatility is compensated by lower returns on all sectors’ returns. After the crisis, as a first step, the TSE widened the price limits, but subsequently, it narrowed them. The results show that the shift from the wider price limit regime to the narrow price limits regime structurally modifies volatility for small and large cap sectors.